Assessment quality of life for patients with cerebro vascular accident - Gourgees, Samira (Iraqi National Journal of Nursing Specialties, 2005)
Abstract : A descriptive study was conducted out patient in Neuralgic Hospital and Teaching Baghdad Teaching Hospital from 1st July / 2004 through October 1st / 2004 . in order to assess with QOL for CVA patients , the study aimed to identifying the QOL domain of ( physical , psychological , level of independence , social and environment ) and it relation with some demographic characteristic which is related to those patients .A purposive sample of ( 50 ) CVA patients who selected from out patient clinic of hospitals . A development questionnaire was structured and is adopted of WHO quality of life questionnaire presented into ( 2 ) parts consist of ( 77 items ) that included 1. demographic data, 2. assessment of CVA patient with QOL domains . Reliability of the study instruments was obtained through test and retest reliability which ( 0.92 ) the content validity questionnaire was determined through panel of experts . Descriptive statistical analysis that used ( frequency , percentage , mean of score ) and inferential statistical analysis (ANOVA , t test) The study findings had revealed that the sub domain of energy and fatigue as part of the physical domain of the quality of life had greatly effected domain had also level independence , environment and social relation ship.The study recommended education program to be developed and implement for patient .